2020
DOI: 10.1109/tec.2019.2953893
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Modeling and Simulation of DFIG-Based Wind Energy Conversion System

Abstract: A multi-scale transients model of a doubly fed induction generator (DFIG)-based wind energy conversion system (WECS) is developed, implemented, and validated. All ac circuit and control quantities of the electrical part are modeled by analytic signals rather than just real signals. In addition to the real parts, the analytic signals also comprise orthogonal imaginary parts. While measured Fourier spectra of real ac quantities involve positive and negative frequency components, they only involve positive freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…where ς = ∆t(k)/∆t(k − 1). On the other hand, the ac quantities with a carrier are calculated by predicting the carrier and shifted phasor separately [21] as…”
Section: B Interfacing Of Multi-scale Model Of the Mmc-hvdc With Its Control Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ς = ∆t(k)/∆t(k − 1). On the other hand, the ac quantities with a carrier are calculated by predicting the carrier and shifted phasor separately [21] as…”
Section: B Interfacing Of Multi-scale Model Of the Mmc-hvdc With Its Control Systemsmentioning
confidence: 99%
“…In recent years, a lot of effort has been devoted to multiscale modeling of the PE-based devices such as two-level VSC. In [20], [21], the multi-scale models of two-level VSC were implemented where the SFM and AVM are alternatively used to modulate the EMTs and electromechanical transients respectively. It was found that the transitions between both models may lead to unpredicted numerical oscillations, not being directly applied in MMC multi-scale modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge in this context is the representation of fast phenomena such as those in power electronic converters in power systems. The transition between EMT and phasor solutions is realised through the application of switching functions [9, 10]. A problem still to be addressed is the integration of power electronic converter models that accurately represent devices inside the converter.…”
Section: Introductionmentioning
confidence: 99%
“…In DPC, the electric network is described through a set of differential rather than algebraic equations, thus being more accurate than QPC models [20]- [26]. DPC-based models have been applied to simulate a broad range of transients in different systems, including unbalanced distribution systems [27], microgrids [25], transients of electric machines [20], [28], and power electronic systems [26], [29], [30]. In all these applications, DPC-based models have demonstrated a good performance for representing the transients under study.…”
mentioning
confidence: 99%